The Impact of Regional Patent Policies on University Technology Transfer: Empirical Evidence from China - Jiafeng Gu (Journal of the Knowledge Economy, 2024)
The low commercialization rate of academic patents is a common challenge for developing countries. This study evaluates the impact of provincial policies on the commercialization of academic patents using spatial regression models and propensity score matching methods. It also provides a reference for optimizing university patent management. Considering provincial patent policies enacted in China in 2016 as the treatment, the results show no significant effect of provincial patent policies on rights definition and implementation economics on the commercialization of academic patents. However, promotion standard policies have a significant positive effect on the commercialization of academic patents. A significant negative spatial spillover effect is observed on the commercialization of academic patents among universities with similar innovation capabilities. Furthermore, non-geographic distances, such as innovation distance, positively affect competition among universities and their commercialization of academic patents. Therefore, local governments should consider the needs of academic inventors for title promotion when designing and introducing patent incentive policies for universities.